Factores de riesgo relacionados con muerte fetal intrauterina en el servicio de ginecología y obstetricia del Hospital Isidro Ayora de Loja periodo junio-agosto de 2013. - Ramón Costa, Germania (2013)
In order to study the socioeconomic risk factors and biological factors relating to stillbirth was conducted this descriptive cross-sectional study in 53 women who had stillbirths admitted to the Department of Gynecology and Obstetrics Hospital Isidro Ayora. Data collection was through medical history and interview. It was found that within the major socioeconomic risk factors are: early maternal age between 15-19 years 45%, 66% single marital status, occupation housewife 49%, 43% primary educational instruction and have had during the pregnancy 57% physical effort. Within cultural factors found exposure to toxic substances among major: medication not prescribed by the doctor 11%. and snuff consumption during pregnancy 10%. Biological risk factors most important in maternal pathologies are pre-pregnancy hypertension with 9%. In nulliparity reproductive background is the main factor with 60%, followed by history of abortion 38%. Among the major complications during pregnancy are presented genito-urinary infections with 72%, followed by 15% preeclampsia and eclampsia. 59% of fetal deaths were early and 30% were late deaths. KEY WORDS: Risk Factors Socioeconomic, Cultural and Biological, Stillbirth, Prenatal and Fetal Death Timeline